2023
DOI: 10.3389/fpubh.2023.1275778
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of vancomycin-resistant enterococci in the United Arab Emirates: a retrospective analysis of 12 years of national AMR surveillance data

Jens Thomsen,
Najiba M. Abdulrazzak,
Hussain AlRand
et al.

Abstract: IntroductionEnterococci are usually low pathogenic, but can cause invasive disease under certain circumstances, including urinary tract infections, bacteremia, endocarditis, and meningitis, and are associated with peritonitis and intra-abdominal abscesses. Increasing resistance of enterococci to glycopeptides and fluoroquinolones, and high-level resistance to aminoglycosides is a concern. National antimicrobial resistance (AMR) surveillance data for enterococci from the Middle East and North Africa (MENA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
1
0
0
Order By: Relevance
“…In line with previous studies, our results also showed that the occurrence of PUTIs in the perioperative period of TH increased hospital costs and the length of hospital stay [ 26 , 34 , 35 ]. Pokrzywa et al [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies, our results also showed that the occurrence of PUTIs in the perioperative period of TH increased hospital costs and the length of hospital stay [ 26 , 34 , 35 ]. Pokrzywa et al [ 36 ].…”
Section: Discussionsupporting
confidence: 92%